2014
DOI: 10.1155/2014/934206
|View full text |Cite
|
Sign up to set email alerts
|

Controversial Issues in Kyphoplasty and Vertebroplasty in Osteoporotic Vertebral Fractures

Abstract: Kyphoplasty (KP) and vertebroplasty (VP) have been successfully employed for many years for the treatment of osteoporotic vertebral fractures. The purpose of this review is to resolve the controversial issues raised by the two randomized trials that claimed no difference between VP and SHAM procedure. In particular we compare nonsurgical management (NSM) and KP and VP, in terms of clinical parameters (pain, disability, quality of life, and new fractures), cost-effectiveness, radiological variables (kyphosis co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 102 publications
(162 reference statements)
4
27
2
Order By: Relevance
“…[10][11][12] Even though conservative treatment continues to be the gold standard in many centers, 8,13 several studies have reported that vertebral augmentation procedures have shown to be an effective treatment, and even superior to conservative treatment in some studies. 6,15,16 In this study, we observed a significant improvement in the patients who were submitted to vertebral augmentation procedures, both in terms of their functionality (ODI) and pain (VAS), which coincides with other similar studies that have been conducted. 6,13,16 It is important to note that there is still controversy around the superiority of either of the vertebral augmentation procedures (kyphoplasty or vertebroplasty).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…[10][11][12] Even though conservative treatment continues to be the gold standard in many centers, 8,13 several studies have reported that vertebral augmentation procedures have shown to be an effective treatment, and even superior to conservative treatment in some studies. 6,15,16 In this study, we observed a significant improvement in the patients who were submitted to vertebral augmentation procedures, both in terms of their functionality (ODI) and pain (VAS), which coincides with other similar studies that have been conducted. 6,13,16 It is important to note that there is still controversy around the superiority of either of the vertebral augmentation procedures (kyphoplasty or vertebroplasty).…”
Section: Discussionsupporting
confidence: 90%
“…8,15 It is for these patients that vertebral augmentation procedures have appeared as an useful alternative in the treatment of OVFs. 6,8,15,16 Among vertebral augmentation procedures, two have shown to be more effective: vertebroplasty and balloon kyphoplasty ( Figure 1). 6,8,16 Vertebroplasty was first described for the treatment of aggressive vertebral hemangiomas of the lumbar spine.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations